CYCLOTRON-RESONANCE OF BOTH MAGNETOPOLARON BRANCHES FOR POLAR AND NEUTRAL OPTIC-PHONON COUPLING IN THE LAYER COMPOUND INSE - Nicholas, R; Watts, M; Howell, D; Peeters, F; Wu, X; Devreese, J; Vanbockstal, L; Herlach, F; Langerak, C; Singleton, J; Chevy, A (1992)
Resonant polaron coupling has been observed by cyclotron resonance of two-dimensional electrons in the polar semiconductor InSe. Both upper and lower branches of the magnetopolaron are seen over a wide range of field (B=18-34 T), allowing an accurate test of polaron theories. A homopolar phonon is also observed to give resonant coupling, via a deformation potential, and we present a theoretical treatment of this coupling mechanism. This gives an accurate value of g2=0.001 0.0005 for the coupling constant. © 1992 The American Physical Society.